2022
DOI: 10.1101/2022.11.16.516610
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Neonatal brain dynamic functional connectivity in term and preterm infants and its association with early childhood neurodevelopment

Abstract: Brain functional dynamics have been linked to emotion and cognition in mature individuals, where alterations are associated with mental ill-health and neurodevelopmental conditions (such as autism spectrum disorder). Although reliable resting-state networks have been consistently identified in neonates, little is known about the early development of dynamic brain functional connectivity and whether it is linked to later neurodevelopmental outcomes in childhood. In this study we characterised dynamic functional… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 149 publications
0
4
0
Order By: Relevance
“…While this is a useful approach to ascertain "on average" characteristics of brain activity, connectivity of the brain is intrinsically dynamic, i.e., non-stationary 3,4 . Addressing this problem, dynamic functional connectivity (dFC) measures the constant neural adjustments needed to control different brain states, adapt to transient situations, and integrate information 5 . The dynamical properties characterising the continuous shifting between connectivity profiles or "states" have been linked to processes such as language 6,7 , cognition [8][9][10][11] , and motor function 12,13 .…”
mentioning
confidence: 99%
“…While this is a useful approach to ascertain "on average" characteristics of brain activity, connectivity of the brain is intrinsically dynamic, i.e., non-stationary 3,4 . Addressing this problem, dynamic functional connectivity (dFC) measures the constant neural adjustments needed to control different brain states, adapt to transient situations, and integrate information 5 . The dynamical properties characterising the continuous shifting between connectivity profiles or "states" have been linked to processes such as language 6,7 , cognition [8][9][10][11] , and motor function 12,13 .…”
mentioning
confidence: 99%
“…Regions related to the motor response to pain (cerebellum, supplementary motor area) were not included. The resulting pain connectome atlas defined on the dHCP 40-weeks PMA T2 standard ( Figure 1 ), was resampled to infant native fMRI space by combining (i) the 40-weeks PMA to each PMA week standard (publicly available, https://git.fmrib.ox.ac.uk/seanf/dhcp-resources/-/blob/master/docs/dhcp-augmented-volumetric-atlas-extended.md) and (ii) the standard to native fMRI warps (non-linear registration based on a diffeomorphic symmetric image normalisation method (SyN) 116 using ANTs, see França et al for details 117 ). The same atlas was also resampled to the adult MNI 152 standard space using dHCP warps (publicly available, https://git.fmrib.ox.ac.uk/seanf/dhcp-resources/-/blob/master/docs/dhcp-augmented-volumetric-atlas-extended.md).…”
Section: Methodsmentioning
confidence: 99%
“…(2021) identified that infants with elevated likelihood for autism show reduced tactile sensory gating. Using MRI indices of functional connectivity, we have reported that the local synchronicity within sensory systems is higher in newborns with a higher likelihood of developing autism (Ciarrusta et al., 2020) and the global network dynamics at full‐term predicts cognitive outcomes and the emergence of later autistic traits (França et al., 2022). We and others have reported similar profiles in autistic adults, namely reduced sensory suppression detected using EEG (Huang et al., 2022) and altered functional connectivity of sensory systems and whole‐brain networks using MRI (Holiga et al., 2019; Watanabe & Rees, 2017).…”
Section: Selecting What Measures To ‘Shift’mentioning
confidence: 99%